The Right of the Adopted Child to Establish and Preserve his Identity. - Ion, Carmen (Acta Universitatis Danubius. Juridica, 2022)
Issues concerning personal identity have not been discussed at the European Union level given the limited competence of the Union in this area. Our paper provides an overview of the issue of fundamental rights related to identity. Some of these rights, such as the right to a name, were mainly claimed as parental rights, however, the approach could be easily transposed to children as well, given the implications for their own rights. Our research aims to identify some essential aspects regarding the right to personal identity, the right to know the origins falls within the scope of the child's right to private life and establishing paternity requires the careful establishment of the balance between the child's interest in knowing the identity and interest of the father presumed or claimed, as well as with the general interest. Also, an adopted child has the right access to information about his or her origin, and biological parents may be granted the legal right not to disclose their identity, but this does not amount to an absolute right of veto.